Studying germplasm collection accessions of naked oats - N. V. Krotova; G. A. Batalova (Труды по прикладной ботанике, генетике и селекции)
Background. The breeding value of accessions from the VIR collection can be estimated only under specific climate and soil conditions. Studying such accessions helps to include them in the breeding process.Materials and methods. Forty-two accessions of naked oats of various origin were studied at the FARC of the North-East. Biochemical analysis of grain and statistical data processing using descriptive statistics and correlation analysis techniques were carried out.Results. The accessions were divided into groups according to their ripening schedule: early (up to 80 days), medium (81–84 days), and mid-late (85–89 days). High yielding genotypes were identified in each ripeness group. The plant height depended on the hydrothermal conditions of the growing season (r = 0.25). The studied accessions were all classified as undersized (64.0–99.1 cm), including the reference cv. ‘Vyatsky’ (88.1 cm). A significant contribution of some panicle productivity components to an increase in yield was observed. The protein and fat content in grain determines its nutritional and energy value. The results showed a positive relationship between yield and protein content (r = 0.44). A significant negative correlation between fat content and protein content (r = –0.61) was registered. The study of naked oat accessions showed different fat content in grain across the ripeness groups.Conclusion. According to the results of the study, some accessions were identified as sources of traits useful for breeding. The following accessions were selected as the best according to a set of characters (yield, plant height, number of grains per panicle, panicle weight, protein and fat content in grain): early ‘Litovsij nagij’ (k-15234, Lithuania), ‘Gkzalon’ (k-15299, Mongolia) and ‘MF9224-164’ (k-15090, USA); medium k-15248 (local, Poland) and MF9521-281 (k-15095, USA); and mid-late ‘Bai Yan 2’ (k-15525, China), ‘Progress’ (k-15339, Russia), ‘Visit’ (k-15501, Ukraine) and ‘Mina’ (k-15192, Bulgaria).